Pengembangan Metode Pembelajaran Klasik Pendidikan Agama Islam Persfektif Imam Al-Ghazali untuk Siswa Inklusi - Komalasari, Komalasari; Zulfah, Machnunah Ani (CENDEKIA, 2022)
This study aims to find out how the steps of inclusive students or with special needs learn and the development of classical learning methods from the perspective of Imam Al-Ghazali in Islamic Religious Education subjects for inclusive students and how effective the development of the classical learning method is. In this development using the R&D development method according to Smith and Regan, this development uses the R&D development method. In this development there is the development of Learning Context Analysis which includes an analysis of needs and environmental characteristics, Analysis of learning characteristics: 1) similarities and differences in learning. 2) Background of learning ability. 3) The implications of learning characteristics on learning design. Analysis of learning tasks: 1) Analysis of learning objectives. 2) Tasks. 3) Learning and learning strategies. 4) Types of learning. Performance appraisal: 1) The purpose of the assessment. 2) Assessment design. 3) Assessment model. The results of the research on the development of classical learning methods, with data collection conducting interviews and observations to teachers and testing classical learning methods on inclusive students. The results of this study are 50% to 60% of inclusive students are able to carry out classical learning methods in Islamic religious education subjects, although 70% of inclusive students are less able to balance learning like normal students and understand all the material presented by the teacher.